ANALISIS EFEKTIVITAS SOSIALISASI PEMILU OLEH DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN KUNINGAN DALAM MENINGKATKAN PARTISIPASI PEMILIH DI WILAYAH PEDASAAN - Hendri Suwarsono; Fathan Rizki H; Dedeh Ermawati; Fachrizal Habbib AN; Ilham Arya Wiguna (STISIP Widyapuri Mandiri, 2025)
This study aims to analyze the effectiveness of election socialization conducted by the Department of Communication and Information of Kuningan Regency in increasing voter participation in rural areas. The method used is a qualitative approach with data collection techniques through interviews and observations. The results show that the socialization conducted is effective in raising awareness and knowledge of the community regarding elections, thus contributing to an increase in voter participation. However, there are challenges in reaching certain community groups, especially in remote areas. This study recommends the use of social media and other interactive methods to further enhance the effectiveness of socialization.